Does caffeine alter muscle carbohydrate and fat metabolism during exercise? - Graham, T. E.; Battram, D. S.; Dela, F.; El-Sohemy, A.; Thong, F. S. L. (Applied Physiology, Nutrition, and Metabolism, 2008)
Caffeine, an adenosine receptor antagonist, has been studied for decades as a putative ergogenic aid. In the past 2 decades, the information has overwhelmingly demonstrated that it indeed is a powerful ergogenic aid, and frequently theories have been proposed that this is due to alterations in fat and carbohydrate metabolism. While caffeine certainly mobilizes fatty acids from adipose tissue, rarely have measures of the respiratory exchange ratio indicated an increase in fat oxidation. However, this is a difficult measure to perform accurately during exercise, and small changes could be physiologically important. The few studies examining human muscle metabolism directly have also supported the fact that there is no change in fat or carbohydrate metabolism, but these usually have had a small sample size. We combined the data from muscle biopsy analyses of several similar studies to generate a sample size of 16-44, depending on the measure. We examined muscle glycogen, citrate, acetyl-CoA, glucose-6-phosphate, and cyclic adenosine monophosphate (cAMP) in resting samples and in those obtained after 10-15 min of exercise at 70%-85% maximal oxygen consumption. Exercise decreased (p < 0.05) glycogen and increased (p < 0.05) citrate, acetyl-CoA, and glucose-6-phosphate. The only effects of caffeine were to increase (p < 0.05) citrate in resting muscle and cAMP in exercise. There is very little evidence to support the hypothesis that caffeine has ergogenic effects as a result of enhanced fat oxidation. Individuals may, however, respond differently to the effects of caffeine, and there is growing evidence that this could be explained by common genetic variations.